California condors and DDT: Examining the effects of endocrine disrupting chemicals in a critically endangered species. (1st April 2016) - Tubbs, Christopher W.
ABSTRACT: In 1987, the last free-flying California condor ( Gymnogyps californianus ) was captured and brought into captivity, rendering the species extinct in the wild. At the time, only 27 condors remained. Today, the population numbers approximately 430 individuals and though condors continue their remarkable recovery, they still face numerous challenges. One challenge, specific to condors inhabiting coastal regions, is exposure to the endocrine disrupting chemical (EDC) p, p '-DDE, through the scavenging of marine mammal carcasses. The exposure levels these birds currently experience appears to be causing eggshell thinning, reminiscent of the phenomenon that nearly collapsed populations of several avian species decades ago. We were interested in further exploring the potential effects of EDCs on California condors. Investigating EDC effects on a critically endangered species like the condor can be difficult, with limited options for studies that can be feasibly conducted. Therefore, we conducted non-invasive, in vitro estrogen receptor (ESR) activation assays to characterize activation by EDCs that coastal condors encounter. Here, I give a brief history of EDCs effects on birds, and in particular the California condor. Additionally, our ESR data are summarized and mechanisms of eggshell thinning are reviewed, highlighting the potential implications of EDC exposure on the continued recovery of the California condor.